A panel of six immune-related mRNAs as biomarkers for tuberculosis diagnosis - Wei, Yutong; Wen, Zilu; Xue, Qinghua; Wang, Lin; Chen, Hui; Shi, Lei; Wan, Laiyi; Li, Leilei; Li, Hongwei; Hao, Wentao; Zhang, Shulin; Wong, Ka-Wing; et al. (Frontiers in Genetics, 2025)
ObjectiveThis study aims to screen common immunological markers of lung tissues and blood for diagnosis of tuberculosis (TB).MethodsDifferentially expressed miRNAs (DEmRs) and mRNAs (DEGs) were obtained by whole-transcriptome sequencing profiles on 18F-FDG PET/CT high and low metabolic active regions in lung tissues of nine TB patients. Common miRNAs were screened by intersecting with DEmRs, four miRNA GEO datasets, and their target mRNAs were predicted through the miRTarbase and Tarbase databases. Then these mRNAs were intersected with DEGs, mRNAs from blood samples and immune-related genes, to construct a miRNA-mRNA interaction network, and the hub genes were identified by Cytoscape. The relationship between immune infiltration and hub genes were evaluated using Cibersort. Finally, a diagnostic model based on Lasso regression analysis was established and validated by qRT-PCR.ResultsFive common miRNAs were obtained in both blood and tissues. Six immune-related mRNAs (NEDD4, PLTP, RNASEL, SEMA7A, TAPBP, and THBS1) were screened out. A diagnostic model was established and validated in the blood samples of 30 pairs (TB/health volunteers). The AUC for the 6-mRNA combination was 0.79.ConclusionWe screened six mRNAs as a combination for diagnosing tuberculosis.